Termorretificação da madeira de alburno de Auxemma oncocalyx (Allemão) Taub. - Sousa, Tallyta Martins de (Universidade Federal Rural do Semi-Árido, 2019)
The aim of this work was evaluate two different temperatures of thermorretification (140 and 200oC) on Auxemma oncocalyx (Pau-branco) sapwood, looking to obtain physical and mechanical properties, as well as a color, close to the heartwood typical values. For that, it was analyzed the specific gravity and dimensional stability, as physical parameters, axial compressive strength, as example of mechanical property, and luminosity, parameter related to the wood color. The results showed that thermorretification temperature of 140oC was high enough to increase the sapwood specific gravity, but at 200oC, duo to a mass loss, an indication of the beginning of a thermal degradation, there was a decrease of the specific gravity value. Still about the use of 200oC temperature, it was possible to conclude that, generally, thermorretification was efficient to lower the sapwood dimensional instability, and was also able to change the wood color to be similar to the heartwood. Concerning to axial compressive strength, the data showed that both temperatures allowed the increase of resistance
Monografia
Keywords: Caatinga; Tratamento térmico; Cerne; Caatinga; Thermal treatment; heartwood; CIENCIAS AGRARIAS::RECURSOS FLORESTAIS E ENGENHARIA FLORESTAL